A new species and two new combinations of Monolophus (Zingiberaceae) from Indo-Burma - Ding, Hong-Bo (PhytoKeys, 2020)
Abstract. Monolophus odontochilus Y.H.Tan & H.B.Ding, a new species from Northern Myanmar, is described and illustrated. The new species is morphologically similar to M. linearis, but differs by having elliptic to oblong leaves (vs. linear-lanceolate to lanceolate), bilobed ligules (vs. entire), purely white corolla (vs. pinkish white), semi-orbicular crenate labellum (vs. trilobed). In addition, a diagnostic key to the new species of Monolophus and its closely related non-yellow flowered species is provided. New combinations are proposed here for Caulokaempferia phokhamii Picheans. & Douangde. and C. wongsuwaniae Picheans. & Douangde. from Laos.